Integrated effects of vermicompost, climatic factors and soil mixing on selected soil fertility indicators (Dhaka University Journal of Biological Sciences, 2023)
A field experiment was carried out to investigate the effects of vermicompost (0, 10, and 15 tha-1), climatic elements i.e. soil moisture (50%, 70%, and 100%) and elevation of soil temperature (1 to 20C) on the physico-chemical properties and nutrient availability of post-harvest calcareous-acid mixed soils after rice production. A total of 18 treatments assembling the afore-mentioned doses was applied. The analyses of the soils demonstrated significant variation in effects (p ≤0.05) of the treatments on both the available nutrient status and the physicochemical properties of soils. Except for available sulfur; soil pH, EC, organic carbon (OC), available nitrogen, phosphorous, potassium, calcium, and sodium were detected in the higher amounts in 1:1 (calcareous : acid-soils) mixed soils than those of 1:3 mixed counterpart both in initial and post-harvest soil conditions. The highest levels of soil pH, OC, available P and Zn were determined in the treatment T13. Whereas, treatment T6 proved to be the best dose for the highest availability of Ca and Mg. The treatments T1, T2, T11, and T16 were recorded to have the lower OC, available N, P, Ca, Mg, Zn and S contents in soils. In particular, the availability of Na was found to be in lesser amounts in all the subplots. In a nutshell, most of the treatments exerted favourable influence in maintaining a healthy level of soil physico-chemical parameters owing to their inherent characteristics.Dhaka Univ. J. Biol. Sci. 32(1): 119-134, 2023 (January)